Using Symmetries à Rebours. Issue 1 (7th October 2020) - Pucci, Edvige; Saccomandi, Giuseppe
Abstract: We consider nonclassical symmetries of partial differential equations (PDEs) in 1 + 1 dimensions. Given a n th‐order ordinary differential equation G = 0 in the unknown w = w ( z ) we are able to find the most general scalar PDE of a given order which can be reduced via a nonclassical symmetry to G = 0 .